Consumer preferences towards animal-friendly fashion products: an application to the Italian market. Issue 6 (25th June 2020) - Achabou, Mohamed Akli; Dekhili, Sihem; Codini, Anna Paola
Abstract : Purpose: This paper aims to examine consumer preference for ethical fashion products by focusing on the importance of animal welfare attribute. To explain the attitude-behavior gap, this research proposes to explore the costs and sacrifices associated with the adoption of responsible behaviors. Design/methodology/approach: To analyze in which manner the animal welfare attribute impacts the consumer preference, the authors carried two quantitative studies in the Italy context. The first one ( n = 224) proposes to measure the importance of this attribute in the case of luxury vs accessible fashion. The second study ( n = 101) examines how the attention given to animal welfare information could vary between prosocials and proselfs. Conjoint analyses that consider "proportion of real fur"; "information about animal treatment" and "price" attributes have been realized. To take into account the individuals characteristics, cluster analysis helped to identify different profiles of consumers. Findings: The results reveal that even if consumers continue to prefer products made entirely from animal fur, they are sensitive to the information on the animal treatment conditions. Also, the animal welfare is not the most important criterion in explaining preference for a fashion product. This result varies, however, regarding the consumers' social value orientation. Individuals with a high level of prosocial values give more importance to the animal welfare attribute and are less reluctant to the reduction of the proportion of real fur in the clothes. Proself consumers associate a higher sacrifice with the consumption of animal-friendly fashion products. Research limitations/implications: This research enriches the limited literature on the consumers' response to animal-friendly products. By considering the consumers' social value orientation, it provides a better understanding of the attitude-behavior gap in animal-friendly fashion consumption. However, further studies should focus on the way of adapting communication on eco-products to the consumer profile. Moreover, it seems interesting to explore how the integration of innovative environmentally friendly materials can be accepted by the target. Replicating this research with representative consumer samples from different countries is also necessary. Practical implications: From a practical point of view, this research offers implications for managers operating in fashion apparel industry by giving insights on the consumers' preference for animal friendly fashion. Social implications: This study gives recommendations to help convincing consumers about the importance of animal welfare attribute and to increase their preference for animal-friendly fashion products. Originality/value: Despite the extensive use of animal fibers, fur and skins in the production of textiles, the few researchers who have shed the light on the consumers' response to animal-friendly products have considered mainly the case of food. Also, the marketing literature gives little explanation of the attitude-behavior gap in ethical fashion consumption. By examining the consumers' social value orientation, this study provides a better understanding of this gap.